Modeling the predictors of students' entrepreneurial intentions: The case of a peripheral European region. Issue 2 (April 2023) - Lopes, João M; Laurett, Rozélia; Ferreira, João J; Silveira, Paulo; Oliveira, José; Farinha, Luís
This study analyzes the predictive factors influencing the entrepreneurial intentions of students at higher education institutions (HEIs) in a peripheral European region. The study includes a sample of 594 students and uses structural equation models for data analysis. The results show that the attitude to behavior and perceived behavioral control positively influence entrepreneurial intention. Furthermore, subjective norms positively impact the attitude to behavior and perceived behavioral control. 'Closer' valuation (i.e., of family, friends, etc) influences attitude to behavior and social valuation positively impacts subjective norms. This research contributes to the literature on entrepreneurial intention as it complements the Theory of Planned Behavior (TPB) with two environmental factors: closer valuation and social valuation. This is important because it provides evidence of whether the environment of the country in question influences entrepreneurial intention and indicates the need for investment in entrepreneurship education. Consequently, the study contributes to the literature by identifying educational factors that may influence students to become entrepreneurs in a peripheral European region. Further, this paper tests the relationship between the attitude towards behavior and subjective norms, perceived behavioral control and subjective norms, something not proposed in the original TPB model.